Vaginal Honey as an Adjuvant Therapy for Standard Antibiotic Protocol of Cervicitis: a Randomized Clinical Trial - Robabeh Hatami; Nazanin Soltani; Narges Forouzideh; Atefeh Kazemi Robati; Mahdi Tavakolizadeh* (Iranian Society of Pharmacognosy, 2022)
Background and objectives: More than half of the cervicitis cases are non-gonococcal and non-chlamydial. Therefore, the cure rate of the principal treatment protocol has reduced to less than 50%. Complementary therapy is an option for adjuvant therapy when standard medical treatment is not effective enough. Honey is used as a natural agent for wound healing and antibacterial effect. This study aimed to compare the effect of honey adjuvant therapy with the standard antibiotic therapy in improving the cure rate of cervicitis. Methods: In this double-blind randomized clinical trial, we enrolled 102 women diagnosed with cervicitis with standard criteria who referred to the gynecological clinic of Mousavi Hospital, Zanjan, Iran. They were randomly divided into two groups. The control group received the oral standard antibiotic treatment plus lubricant gel as placebo, and the intervention group received the oral standard treatment plus vaginal Ziziphus honey as adjuvant therapy. Both groups received the treatment once a day for two weeks. The symptoms and clinical findings of the patients were evaluated for three weeks following the initiation of the treatments. Results: All clinical symptoms of cervicitis significantly decreased after the treatment in both groups (p≤0.05), but the vaginal discharge of the intervention group reduced more (p≤0.05). In addition, the intervention group showed better results for the restoration of cervical erosion in comparison with the control group (p<0.05). Conclusion: Vaginal honey adjuvant therapy can improve the efficiency of standard antibiotic treatment to reduce the clinical symptoms of cervicitis.